Low Memory T Cells Blood Counts and High Naïve Regulatory T Cells Percentage at Relapsing Remitting Multiple Sclerosis Diagnosis - Canto-Gomes, João; Silva, Carolina S.; Rb-Silva, Rita; Boleixa, Daniela; da Silva, Ana Martins; Cheynier, Rémi; Costa, Patrício; González-Suárez, Inés; Correia-Neves, Margarida; Cerqueira, João J.; Nobrega, Claudia (Frontiers in Immunology, 2022)
Objective: To assess the peripheral immune system of newly diagnosed relapsing remitting multiple sclerosis (RRMS) patients and compare it to healthy controls (HC). Methods: Cross-sectional study with 30 treatment-naïve newly diagnosed RRMS patients, and 33 sex and age-matched HC. Peripheral blood mononuclear cells were analyzed regarding: i) thymic function surrogates [T cell receptor excision circles (TRECs) and recent thymic emigrants (RTEs)]; ii) naïve and memory CD4+ and CD8+ T cells subsets; iii) T helper (Th) phenotype and chemokine receptors expression on CD8+ T cells subsets; iv) regulatory T cell (Tregs) phenotype; and vi) expression of activating/inhibitory receptors by natural killer (NK) and NKT cells. Analyses were controlled for age, sex, and human cytomegalovirus (HCMV) IgG seroprevalence. Results: Newly diagnosed RRMS patients and HC have equivalent thymic function as determined by similar numbers of RTEs, and levels of sjTRECs, DJβTRECs and sj/DJβTREC ratio. In the CD8+ T cells compartment RRMS patients have a higher naïve/memory ratio and lower blood memory cell counts, specifically of effector memory and TemRA CD8+ T cells. Interestingly, higher numbers and percentages of central memory CD8+ T cells are associated with increasing time from relapse. Among CD4+ T cells, lower blood counts of effector memory cells are found in patients upon controlling for sex, age and anti-HCMV IgG seroprevalence. Higher numbers of CD4+ T cells (both naive and memory) and of Th2 cells are associated with increasing time from the relapse; lower numbers of Th17 cells are associated with higher MS severity scores (MSSS). RRMS patients have a higher percentage of naive Tregs compared to HC, and lower percentages of these cells are associated with higher MSSS. Percentages of immature CD56bright NK cells expressing the inhibitory receptor KLRG1, and of mature CD56dimCD57+ NK cells expressing NKp30 are higher in patients. No major alterations are observed on NKT cells. Conclusion: Characterization of the peripheral immune system of treatment-naïve newly diagnosed RRMS patients unveiled immune features present at clinical onset including lower memory T cells blood counts, particularly among CD8+ T cells, higher percentage of naïve Tregs and altered percentages of NK cells subsets expressing inhibitory or activating receptors.